Zero‐Valent Iron Immobilized on Multi‐Walled Carbon Nanotubes for Heterogeneous Catalytic Ozonation of Methylene Blue as Model Compound. Issue 5 (17th October 2013) - Zhang, Shuo; Wang, Dong; Zhang, Xingwen; Fan, Pingping
<x xml:space="preserve">Abstract</x> This paper reported a novel ozone catalyst capable of working on acidic solution environments (labeled as CNTs‐Fe0), which was prepared by immobilizing zero‐valent iron particles onto the surface of multi‐walled carbon nanotubes. The catalytic effect of CNTs‐Fe0 during ozonation was studied in terms of, degradation of methylene blue as model compound and concentration profile of hydroxyl radicals (HO). At pH 3, the production of HO was sharply accelerated in the presence of CNTs‐Fe0 about 80 times compared to that obtained by plain ozone, resulting in the intensification of mineralization that was considered to occur mainly in the liquid bulk. In addition to the direct catalytic pathway, a carbon‐surface‐mediated Fenton‐like pathway possibly took place as another important route accounting for the catalytic activity of CNTs‐Fe0. The role of CNTs substrate during ozonation was evaluated, and it would act as an effective "promoter" rather than ozone catalyst for acidic pH around 3 where CNTs‐Fe0 optimally works.